2000
DOI: 10.1038/sj.gene.6363699
|View full text |Cite
|
Sign up to set email alerts
|

Allele associations reveal four prominent haplotypes at the human interleukin-6 (IL-6) locus

Abstract: We have examined four polymorphic elements in the human interleukin-6 (IL-6) locus and described their allele distribution in 73 unrelated, healthy individuals from the West-of-Scotland. These comprised three single nucleotide polymorphisms (SNP) in the 5Ј promoter region of the gene and one VNTR in the 3Ј region of IL-6. A statistical consideration of the relationship between alleles at each locus was carried out. Of a total of 12 possible haplotypes observed in the population, the analysis suggested that fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
(46 reference statements)
2
13
1
Order By: Relevance
“…The -174G>C polymorphism in the promoter region of IL-6 is considered to regulate IL-6 production (9,26,31) and is associated with juvenile chronic arthritis (28) and myocardial infarction in Caucasians (25). In the present study, -174G>C was not identified, although this SNP is commonly detected with about a 40% prevalence in Caucasians (13,25,28,31,32). In contrast, -636G>C, which we clarified to have a significant association with blood pressure and carotid IMT in Japanese women, has been recognized with only about a 5% prevalence in Caucasians (13,25,32).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The -174G>C polymorphism in the promoter region of IL-6 is considered to regulate IL-6 production (9,26,31) and is associated with juvenile chronic arthritis (28) and myocardial infarction in Caucasians (25). In the present study, -174G>C was not identified, although this SNP is commonly detected with about a 40% prevalence in Caucasians (13,25,28,31,32). In contrast, -636G>C, which we clarified to have a significant association with blood pressure and carotid IMT in Japanese women, has been recognized with only about a 5% prevalence in Caucasians (13,25,32).…”
Section: Discussioncontrasting
confidence: 40%
“…In the present study, -174G>C was not identified, although this SNP is commonly detected with about a 40% prevalence in Caucasians (13,25,28,31,32). In contrast, -636G>C, which we clarified to have a significant association with blood pressure and carotid IMT in Japanese women, has been recognized with only about a 5% prevalence in Caucasians (13,25,32). In the African-American population, -636G>C is common (9.5%) and -174G>C is rare (4%), findings which are very different from those for Caucasians (30); however, circulating IL-6 levels in African-Americans are similar to those in Caucasians (31).…”
Section: Discussionmentioning
confidence: 74%
“…For genotyping the TNF-α (-308 G/A, -857 C/T, -863 C/A, -1031 T/C) polymorphism, the PCR products for each polymorphism was digested with NcoI, HpyCHIV, HpyCHIV, and BbsI, respectively (Skoog et al 1999). IL6 (-172 G/C, -570 G/C, -594 G/A) polymorphism was genotyped by PCR and subsequent restriction digestion with NlaIII, Fnu4H-I and FokI, respectively (Jordanides et al 2000). Genotyping of IL8, -251 A/T polymorphism was performed by digestion of the PCR products with the restriction enzyme MfeI.…”
Section: Diagnosis Of H Pylori Infectionmentioning
confidence: 99%
“…the gastric mucosa. Polymorphisms in IL-1B, IL6, IL8 and TNF-α have been reported to influence cytokine expression, thereby influencing inflammatory processes in response to infectious diseases (Graham 1997;Jordanides et al 2000;ElOmar et al 2001a,b;Hull et al 2001;McColl and El-Omar 2002). Recent studies have described the association of specific variants of the IL-1B and TNF-α genes with susceptibility to H. pylori-related diseases (Kato et al 2001;El-Omar et al 2003;Garcia-Gonzalez et al 2003;Lee et al 2003;Chakravorty et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Genetic studies have identified four polymorphisms in the promoter region of the IL-6 gene (-597G/A, -572G/C, -373A/T, -174G/C) that have significant effect on IL-6 expression in an in vitro system [80,116,117]. A variable number of tandem repeat (VNTR) polymorphisms were found in the 3 0 flanking region of the IL-6 gene (C allele) [9].…”
Section: Zinc-interleukin-6 Gene Interactionmentioning
confidence: 99%